2017
DOI: 10.1136/bmjopen-2016-012934
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative study of the BREATHER trial (Short Cycle antiretroviral therapy): is it acceptable to young people living with HIV?

Abstract: ObjectivesA qualitative study of the BREATHER (PENTA 16) randomised clinical trial, which compared virological control of Short Cycle Therapy (SCT) (5 days on: 2 days off) with continuous efavirenz (EFV)-based antiretroviral therapy (CT) in children and young people (aged 8–24) living with HIV with viral load <50 c/mL to examine adaptation, acceptability and experience of SCT to inform intervention development.SettingPaediatric HIV clinics in the UK (2), Ireland (1), the USA (1) and Uganda (1).ParticipantsAll … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…It was the first HIV/AIDS treatment center in Uganda to provide ART and is currently the country’s only reference center for third-line therapy. The study was embedded within a clinical trial ( 36 ) (BREATHER) which was testing the efficacy of a treatment interruption intervention, Short Cycle Therapy on efavirenz-based regimens (5 days on, 2 days off treatment) for young people (8–24 years) living with HIV ( 37 ).…”
Section: Methodsmentioning
confidence: 99%
“…It was the first HIV/AIDS treatment center in Uganda to provide ART and is currently the country’s only reference center for third-line therapy. The study was embedded within a clinical trial ( 36 ) (BREATHER) which was testing the efficacy of a treatment interruption intervention, Short Cycle Therapy on efavirenz-based regimens (5 days on, 2 days off treatment) for young people (8–24 years) living with HIV ( 37 ).…”
Section: Methodsmentioning
confidence: 99%
“…This model has been used in a few new trials (e.g. D3, BREATHER-plus, LATA) in children, adolescents and young people led by Penta and/or the Clinical Trials Unit at the University College of London [33].…”
Section: Designing Specific Clinical Trial Materials For Adolescentsmentioning
confidence: 99%
“…The qualitative study consisted of repeat in-depth interviews with a sample of participants from both arms of the trial, and discussion groups at the end to discuss emerging trial results. The qualitative data showed that while there was a strong preference for the option of short-cycle therapy, to allow weekends off from treatment, young people from both arms reported frequent medication side effects and occasional missed doses that they had rarely shared with clinical staff [34]. The final discussion group allowed participants to voice concerns about the risks of short-cycle therapy for young people who struggled to adhere to treatment [35].…”
Section: A Multi-country Trial To Develop a Treatment Intervention mentioning
confidence: 99%
“…It should be noted that while some of the qualitative study findings were integrated into the "main" trial paper the paper [17] detailing the qualitative findings (which was submitted at the same time as the main trial findings paper) was not accepted for publication. The qualitative findings paper was published later in a different journal [34].…”
Section: A Multi-country Trial To Develop a Treatment Intervention mentioning
confidence: 99%